Democracy and human rights in multicultural societies - Koenig, Matthias; Guchteneire, P. F. A. de (Ashgate [u.a.], 2007)
By unanimous adoption of the Universal Declaration of Cultural Diversity, the UNESCO Member States accepted a new ethical approach to respect diversity as a guiding principle for democratic societies. While support for the Declaration remains strong, there is a general awareness that the democratic management of multicultural societies needs rethinking and further development. This publication examines the political governance of cultural diversity, specifically how public policy-making has dealt with the claims for cultural recognition that have increasingly been expressed by ethno-national movements, language groups, religious minorities, indigenous peoples and migrant communities. Its principle aim is to understand, explain and assess public policy responses to ethnic, linguistic and religious diversity. Adopting interdisciplinary perspectives of comparative social sciences, the contributors address the conditions, forms, and consequences of democratic and human-rights-based governance of multi-ethnic, multi-lingual and multi-faith societies.--Publisher's description